LITERASI LINGKUNGAN DALAM MENGUATKAN PERILAKU PEDULI LINGKUNGAN SISWA: STUDI KASUS EKSTENSIF DI MI MA’ARIF BANDUNGGEDE - Jumrotul Nur Aisah; Ahmad Labib (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study was motivated by the decline in the consistency of ecological programs following the Adiwiyata evaluation at MI Ma’arif Bandunggede, Temanggung Regency, which led to deviations in students’ environmental behavior, such as poor waste management and excessive energy consumption. Employing a descriptive-explanatory qualitative case study design, this research explored in depth the environmental literacy and psychomotor manifestations of fourth- and fifth-grade students. Data were collected through prolonged participant observation, in-depth semi-structured interviews with the principal, teachers, and student representatives, and were further supported by an audit of the school’s environmental portfolio documentation. Data trustworthiness was established through triangulation of techniques, sources, and time. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, encompassing data reduction, categorization, matrix-based data display, and conceptual verification. The findings revealed that, prior to the intervention, students’ environmental literacy was at the functional-nominal level, characterized by rote memorization and incidental understanding, which failed to foster independent and sustainable environmental practices. However, following the implementation of a two-phase interactive reinforcement model consisting of contextual theoretical re-education and project-based guided habituation, students demonstrated a significant improvement toward operational environmental literacy. This progress was reflected in the internalization of environmental values, as evidenced by improved classroom cleanliness management, more efficient electricity use, reduced daily plastic waste, and greater concern for the preservation of the school’s vegetation. The study concludes that consistent and practice-oriented environmental literacy reinforcement has a positive linear relationship with the development of students’ environmental care character and contributes to the sustainable revitalization of the Adiwiyata School culture.